Prime-number-assisted block-based neighbor discovery protocol in wireless sensor networks - Woosik Lee; Jong-Hoon Youn; Teukseob Song (International Journal of Distributed Sensor Networks)
During the initial deployment time, wireless sensors continually search their neighbors. The neighbor discovery is not an one-time event because the network topology can be changed anytime due to node mobility and failure. The neighbor discovery protocol helps sensor nodes to find neighboring sensors within their communication range. This study proposes a novel neighbor discovery protocol called the prime-number-assisted block-based neighbor discovery protocol, which intelligently changes the sensor schedules based on the greater common divisor of two sensors’ discovery cycle lengths. For example, for two sensors whose duty cycles are different, if the lengths of their discovery schedules are relatively prime, the prime-number-assisted block-based neighbor discovery protocol simply uses the balanced incomplete block design–based neighbor discovery protocol without adding any additional active slots; otherwise, it changes the original balanced incomplete block design–based schedule using a prime number. In this study, we compare the performances of prime-number-assisted block-based neighbor discovery protocol and other recently proposed neighbor discovery protocols (U-Connect, Disco, SearchLight, and Hedis) using a TOSSIM simulator. The experimental results confirm the superiority of prime-number-assisted block-based neighbor discovery protocol over other neighbor discovery protocols in terms of discovery latency and energy consumptions.